Introducing the EdTech Hub’s programme for research in low-income countries – The EdTech Hub - Hennessy, Sara (EdTech Hub, 2019)
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Research publication strategy and proposed publications - Haßler, Björn; McIntyre, Nora; Hollow, David; Jordan, Katy; Hennessy, Sara; Brugha, Meaghan; Mitchell, Joel (EdTech Hub, 2019)
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Systemic Mixed-Methods Research — A conceptual framework for EdTech research along the IDIA scale - Haßler, Björn; Hennessy, Sara; Hollow, David; Simpson, Lea; Carter, Alice; Damani, Kalifa; Francis, Gill; Jordan, Katy; McIntyre, Nora; Mitchell, Joel (EdTech Hub, 2019)
Keywords: LP: English; R:Mixed methods; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF; _yl:f; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
Keywords: LP: English; R:Literature review, systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology, EdTech, low-income countries, literature review

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Methodology for literature reviews undertaken by the EdTech Hub - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Sara Hennessy; David Hollow; Katy Jordan; Kevin Martin; Mary Murphy; Hannah Walker (EdTech Hub, 2019)
An output of the EdTEch Hub
Keywords: LP: English; R:Literature review, systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _dont_post_PDF; _yl:h; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode